Description Of Depression Tendency On Adolescent Private Vocational School Due To Dating Violence At Integrated Service Centers For Empowerment Of Women And Children In Tangerang - Siti Nadiya Akmaliya; Triana Indrayani; Andi Julia Rifiana (UrbanGreen, 2020)
Dating relationship is adolescence’s activity marked by interest and with uncertainty. In some dating relationships, there are violent cases. The incidence of dating relationship is the efforts that causes of having and striving to control or dominate others physically, psychologically, and sexually. Sexual violence in dating violence experienced by young women leads to a loss that affects the future and leads to depression. Depression is a serious condition that can influence the youth's behaviors, emotions, and ways of thinking, as well as a permanent nature that requires serious handling from various parties. This research used a descriptive approach aimed at finding out the sense of depression tendencies occurring in young women who had sexual violence in dating violence. In the results of this research found that the average victim of young women resulting from dating violence suffered from depression after the incident, and refused to meet again with the abuser after experiencing sexual violence in dating violence. Perilaku pacaran adalah semua kegiatan atau aktivitas pada masa remaja yg ditandai dgn ketertarikan dan disertai ketidakpastian. Dalam beberapa hubungan pacaran, terdapat kasus kekerasan. Kekerasaan dalam pacaran ialah upaya-upaya yang timbul akibat dari rasa memiliki dan berupaya untuk mengendalikan atau mendominasi orang lain secara fisik, psikologis dan seksual. Kekerasan seksual dalam dating violence yang dialami oleh remaja perempuan menimbulkan kerugian yang berdampak pada masa depan dan berujung mengalami depresi. Depresi merupakan merupakan sebuah kondisi yang serius yang dapat memengaruhi perilaku, emosi, dan cara berpikir para remaja tersebut, serta sifatnya yang permanen yang membutuhkan penanganan serius dari berbagai pihak. Penelitian ini menggunakan pendekatan deskriptif yang bertujuan untuk mengetahui gambaran tendensi depresi yang terjadi pada anak remaja perempuan yang mengalami kekerasan seksual dalam dating violence. Dalam hasil penelitian ditemukan bahwa rata-rata korban remaja perempuan akibat dari dating violence mengalami depresi setelah kejadian, dan menolak untuk bertemu lagi dengan pelaku setelah mengalami kekerasan seksual dalam dating violence.